2021
DOI: 10.1177/0266666920983393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ICT skills on job performance of librarians in university libraries of South-South, Nigeria

Abstract: The study examined the influence of information and communication technology (ICT) skills on job performance among librarians in the university libraries in South-South, Nigeria. The study adopted a descriptive survey design using a self constructed questionnaire as instrument for data collection. The questionnaire was constructed after consulting other related literature in order to ensure that relevant items were included. Five research questions were answered in the study. The population consists of 233 lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A digital library is a digital information material system supported by modern technology, and it is the next-generation information resource management model of China's Internet. The digital library is an important achievement of the comprehensive digitization of Chinese library collections [ 11 , 12 ], and the university library refers to the library that serves the teaching and scientific research of higher education, and is the document and information center of higher education. With the rapid development of science and technology, traditional libraries cannot meet the current needs of people's learning, and are developing in the direction of digital libraries.…”
Section: Theoretical Knowledge and Methodsmentioning
confidence: 99%
“…A digital library is a digital information material system supported by modern technology, and it is the next-generation information resource management model of China's Internet. The digital library is an important achievement of the comprehensive digitization of Chinese library collections [ 11 , 12 ], and the university library refers to the library that serves the teaching and scientific research of higher education, and is the document and information center of higher education. With the rapid development of science and technology, traditional libraries cannot meet the current needs of people's learning, and are developing in the direction of digital libraries.…”
Section: Theoretical Knowledge and Methodsmentioning
confidence: 99%
“…Librarians were selected as the respondents in this study because they have records on the usage of special collections during the COVID-19 pandemic period in the various libraries under study. According to a study by Oyovwe-Tinuoye et al (2021:5), there is a total of 233 academic librarians in the federal, state and private universities in the South South zone of Nigeria: ‘Among these universities, 95 respondents are from the federal universities, 93 of the respondents are from the state universities while 45 of the respondents are from the private universities given a total of 233’. This study therefore adopted the population of 233 as its sample.…”
Section: Methodsmentioning
confidence: 99%
“…From the consulted literature, it is clear that there is death of empirical literature on the application of AI-powered tools in research writing by LIS professionals in Nigeria, despite the widely proclaimed potentials of the tools in transforming education and research. Generally, some studies by Oyovwe-Tinuoye et al [22]; Udo-Anyanwu [23]; Aina et al [24]; Akwang [25] and many others revealed a low level of application of emerging technologies among LIS professionals in Nigeria. However, few recent empirical studies about AI-powered tools applications for research writing and professional purposes were reviewed.…”
Section: Empirical Review On Application Of Ai-powered Tools In Resea...mentioning
confidence: 99%